(untitled) - David, Andrej (Doprava a spoje, 2012)
The port of Rotterdam is the biggest container port in Europe. In the part Maasvlakte 1 there are three container terminals which can serve container vessels Super Post Panamax. Two of them (ECT Delta and Euromax) belong to the company ECT. These terminals use automatic stacking cranes and AGV system for handling of containers due to the increase of throughput and the reduction of downtime during handling. APM terminal uses straddle carriers for handling of containers between quayside cranes and the blocks of the container yard.